Persepsi Orang Tua Terhadap Dampak Penggunaan Gadged Pada Anak Usia 4-6 Tahun - Lily, Netry Maria; Norlianti Lusia Tabun; Martheda Maarang; Petrus Mau Tellu Dony (Early Childhood: Jurnal Pendidikan, 2025)
Gadgets are one real example of how science and technology have advanced and developed rapidly in the modern era. Children use gadgets for various needs and desires, including accessing themed books, picture books, in addition children use gadgets to watch YouTube, access katrun films, and what is more familiar now is to play online games. It is very important for parents to control children in using gadgets because it greatly affects the growth and development of children. The purpose of this study was to find out how parents perceive the impact of gadget use on children aged 4-6 years in Kalabahi City, Teluk Mutiara District, Alor Regency. The method used in this study is descriptive quantitative with descriptive statistical analysis and data collection techniques were carried out using a questionnaire using a Likert scale measurement. The findings of this study indicate that there are 44% of parents who believe that gadgets have a negative impact on children so that they limit the use of gadgets and control their children when using gadgets, but there are also 56% of parents who believe that gadgets have a positive impact on children so that they allow their children to use gadgets as they please so that parents are also free to do their activities.